The red balloon and other stories [videorecording (DVD)] - Lamorisse, Albert; Colomb de Daunant, Denys, 1922-2006; Lamorisse, Pascal; Sellier, Georges, 1893-1988; Popov, Vladimir A.; Emery, Alain; Grenier, Jean-Pierre; Strauss, Peter, 1947-; Prévert, Jacques, 1900-1977; Prévert, Jacques, 1900-1977; Gille, André, 1921-2012; Baquet, Maurice, 1911-2005; et al. (Criterion collection, 2023)
The red balloon: A French boy named Pascal discovers a stray red balloon in the streets of Paris. Pascal and the balloon become fast friends and share many adventures.